Agronomic performance of soybean grown in succession to winter cover crops - Krenchinski, Fabio Henrique [UNESP]; Cesco, Victor Jose Salomao [UNESP]; Rodrigues, Danilo Morilha [UNESP]; Albrecht, Leandro Paiola; Wobeto, Katle Samaya; Albrecht, Alfredo Junior Paiola (Empresa Brasil Pesq Agropec, 2018)
The objective of this work was to evaluate the effect of winter cover crop species on the agronomic performance of soybean (Glycine max) cropped in succession, under a no-tillage system. The study was conducted during three crop seasons (2011/2012, 2012/2013, and 2013/2014), with the following cover crops: white oat (Avena sativa), black oat (Avena strigosa), ryegrass (Lolium multiflorum), vetch (Vicia sativa), forage radish (Raphanus sativus), the intercrop black oat + forage radish, and wheat (Triticum aestivum) as the standard management. Forage radish and the intercrop black oat + forage radish provided greater soil cover rates after 30 days of planting, as well as dry matter production in the three crop seasons. After 45 and 90 days from desiccation, however, white oat and ryegrass showed the highest soil cover rate. Black oat and the intercrop black oat + forage radish provided higher soybean yield than the standard management with wheat, in the 2012/2013 and 2013/2014 crop seasons. Winter cover crops can significantly affect soybean yield in succession, and black oat and the intercrop black oat + forage radish stand out for this purpose.
Keywords: Glycine max; crop rotation; mulching; no-tillage; soil cover